Victim Protection and The Dynamic Situation of Human Trafficking: Indonesia Experience - Naibaho, Nathalina (Indonesian Journal of International Law, 2023)
Human trafficking is a global issue. It can arise in the context of national and/or transnational acts and are regulated by national and transnational criminal law mechanisms. However, in trafficking in person cases there are links between human trafficking and other related crimes such as drugs trafficking. Meanwhile, Indonesia has enacted laws which provide mandatory protection for victims of human trafficking. It also has mandatory drug laws which, in some cases, subject to the death penalty. This legislative conflict together with investigative and prosecutorial failure risks the conviction of human trafficked victims who are used as drug dealers in organized crime activities. The drugs offenders will sentence under the criminal law if the act of the offender fit with the element of crime under narcotic law. This paper will examine the intersections between victimology and Indonesian laws which the recent cases before Indonesian courts have demonstrated that enacted laws are not being applied properly which allows for the protection of trafficked victims forced into the drug trafficking. Dynamic situation that has been the highlight is a principle which is contained within Indonesian legislation, and which reflects the emerging norm of non-prosecution of victims in international legal discourse. This article suggests a new approach to statutory interpretation with the need for effective mechanisms that, if adopted, will enable Indonesia to lead a new approach to victim protection.